A critical perspective on interpreting amplicon sequencing data in soil ecological research. (September 2021) - Alteio, Lauren V.; Séneca, Joana; Canarini, Alberto; Angel, Roey; Jansa, Jan; Guseva, Ksenia; Kaiser, Christina; Richter, Andreas; Schmidt, Hannes
Abstract: Microbial community analysis via marker gene amplicon sequencing has become a routine method in the field of soil research. In this perspective, we discuss technical challenges and limitations of amplicon sequencing and present statistical and experimental approaches that can help addressing the spatio-temporal complexity of soil and the high diversity of organisms therein. We illustrate the impact of compositionality on the interpretation of relative abundance data and discuss effects of sample replication on the statistical power in soil community analysis. Additionally, we argue for the need of increased study reproducibility and data availability, as well as complementary techniques for generating deeper ecological insights into microbial roles and our understanding thereof in soil ecosystems. At this stage, we call upon researchers and specialized soil journals to consider the current state of data analysis, interpretation, and availability to improve the rigor of future studies. Highlights: Soil complexity necessitates careful interpretation of sequencing data. Studies often do not account for data compositionality, leading to misinterpretation. Functions should not be inferred from phylogeny as they are rarely conserved. We discuss complementary approaches that help to improve ecological insights. We call for journals and authors to improve study reproducibility and data availability.